Holographic interferometry of AIRSAR data for modelling rate change of shoreline - Marghany, Maged (2007)
Malaysian researchers and scientists are required to design a new sensor which might be different than TuingSAT-1 and RAZAKSAT microsatellites in term of its physical properties and application too. Multi-polarized sensor has tremendous use in the coastal zone studies. In addition, polarized sensor is able to investigate the coastal problems such as erosion and sedimentation. AIRSAR polarized sensor could be an ideal concept in developing such sensor. In this context, this work is introducing a new approach for modeling shoreline change rate from AIRSAR Cvv-band. The hologram algorithm has been applied to simulate the wave spectra propagation pattern. Furthermore, Doppler frequency and azimuth cut off model are used to model longshore current movement and rate change of sediment transport volume. The results shows that the phase information of AIRSAR hologram image can be used to simulate the wave refraction pattern. Shoreline change rate is less than -0.5m /day which indicates an erosion event with accuracy error of ± 0.05 m/day.